Pengaruh Kualitas Pelayanan, Word Of Mouth Dan Kepercayaan Terhadap Kepuasan Konsumen Dalam Menggunakan Transportasi Online Maxim Di Kota Sorong - Wilda Aulia Rahma; Karfin; Rokhimah; Erna kurniawatih (At-Thariqah: Jurnal Ekonomi, 2025)
This study aims to determine the influence of Service Quality, Word of Mouth (WOM), and Trust on Consumer Satisfaction when using Maxim online transportation in Sorong City.This study used a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis techniques, processed using the SmartPLS 4 application. The sample in this study consisted of 100 consumers who used Maxim online transportation in Sorong City.The results showed that Service Quality did not significantly influence consumer satisfaction among Maxim users in Sorong City. Meanwhile, Word of Mouth and Trust significantly influenced consumer satisfaction. The coefficient of determination (R2) was 0.716, indicating that the model was able to explain 71.6% of the variability in consumer satisfaction among Maxim users. This study concluded that increased consumer satisfaction was more influenced by Word of Mouth and Trust than by service quality.